+0  
 
0
487
2
avatar

x² -22x -2x +44 c) -x² -8x -3x -24 +x² -22x -2x +44

 12.05.2015

Beste Antwort 

 #1
avatar+14537 
+3

x²-22x-2x+44           |  -22x-2x = -24x

 

= x² -24x +44

 

-x²-8x-3x-24+x²-22x-2x+44      | -x²  und  +x²  heben sich auf,  alle x zusammnegefasst = -35x

 

                                                 | -24 +44 = +20

 

= -35x +20

 

Gruß radix !

 12.05.2015
 #1
avatar+14537 
+3
Beste Antwort

x²-22x-2x+44           |  -22x-2x = -24x

 

= x² -24x +44

 

-x²-8x-3x-24+x²-22x-2x+44      | -x²  und  +x²  heben sich auf,  alle x zusammnegefasst = -35x

 

                                                 | -24 +44 = +20

 

= -35x +20

 

Gruß radix !

radix 12.05.2015
 #2
avatar
0

Danke  (y)

 12.05.2015

39 Benutzer online

avatar
avatar
avatar
avatar
avatar